Studies on genus Lactarius from India - N.S. ATRI, S.S. SAINI and (Indian Phytopathology, 2002)
In the present paper, five taxa of Lactarius Gray belonging to subgenus Lectifluus (Pers.) Roussel are included and key to their identification given. These are L. piperatus, var. piperatus (Fr.) S. F. Gray, L. angustifolius Hesler & Smith, L. corrugis Peck, L. volemus var. flavus Hesler & Smith and L. volimus (Fr.) Fr. Out of these , the first four taxa are new records for India.